Neoadjuvant chemotherapy or chemoradiotherapy for adenocarcinoma of the esophagus. Issue 8 (28th May 2018) - Visser, Els; Edholm, David; Smithers, B. Mark; Thomson, Iain G.; Burmeister, Bryan H.; Walpole, Euan T.; Gotley, David C.; Joubert, Warren L.; Atkinson, Victoria; Mai, Tao; Thomas, Janine M.; Barbour, Andrew P.
Abstract : Background: The optimal treatment strategy for patients with esophageal adenocarcinoma (EAC) remains undetermined. This study compared outcomes in patients undergoing neoadjuvant chemotherapy (nCT) and neoadjuvant chemoradiotherapy (nCRT) for EAC. Methods: Patients who underwent nCT or nCRT followed by surgery for EAC were identified from a prospective database (2000‐2017) and included. After propensity score matching, the impact of the treatments on postoperative complications, in‐hospital mortality, pathological outcomes, and survival rates were compared. Results: Of the 396 eligible patients, 262 patients were analysed following matching with 131 patients in both groups. There were no significant differences between the nCT and nCRT groups for overall complications (59% vs 57%, P = 0.802) or in‐hospital mortality (2% vs 0%, P = 0.156). Patients who had nCRT had more R0 resections (93% vs 83%, P = 0.013), and higher pathological complete response rates (15% vs 5%, P < 0.001). No differences in 5‐year overall survival rates (nCT vs nCRT; 44% vs 33%, P = 0.645) were found. Conclusion: In this study no differences between nCT and nCRT were seen in postoperative complications and in‐hospital mortality in patients treated for EAC. Inspite of improved complete resection and pathological response there was no difference in the overall survival between the treatment modalities.